Broadcasting, Voice, and Accountability : A Public Interest Approach to Policy, Law, and Regulation - Buckley, Steve; Duer, Kreszentia; Mendel, Toby; Siochru, Sean O. (Washington, DC: World Bank, 2013)
The broadcast media, radio and television, have a unique and particular role to play both in enhancing governance and accountability and in giving voice to poor and marginalized communities. Broadcast media, are especially relevant and accessible to remote communities, cultural and linguistic minorities, the very poor and illiterate people. Policies, laws, regulations, and other public actions that govern the broadcast media are central to play that role, and they form the main focus of this guide. The guide maps out a public interest approach to fostering free, independent, and pluralistic broadcast media. Its objective is to provide guidance on how to design a policy, legal, and regulatory framework that can contribute to the achievement of public interest goals such as transparency of government and accountability to the people, enhanced quality of and participation in public debate, and increased opportunities for marginalized groups to develop and articulate their views. The guide draws from the experiences of a wide range of countries in all regions of the world and is illustrated extensively by country-level examples of policies, laws, and regulations. The guide is intended as a tool for media reform particularly in developing and transitional democracies. This guide is structured as follows: part one offers an overview of the rationale for a public interest approach and its role in enhancing governance, development, and voice. Part two examines the general enabling environment for media and communications, including standards of freedom of expression and access to information, the use and misuse of defamation law, and general content rules that apply to all media, including print media and journalists. Part three is dedicated specifically to broadcasting, including the role of regulatory bodies, broadcast content rules, the distinctive sectors commonly referred to as public service, community nonprofit, and commercial private sector broadcasting, as well as the regulation of broadcast spectrum and channels. The final section of the guide presents a research agenda that is intended to address the lack of relevant and systematic data and information on broadcasting encountered during the process of researching and compiling this guide. It concludes by presenting some options and practical opportunities for development assistance to support a more coherent approach to reforming broadcasting in the public interest.